Effect of cow vermicompost on growth, fruit yield, and quality of hot pepper (Capsicum annuum var. Red chili) - Mohammad Hossein Aminifard (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study evaluated the response of hot pepper (Capsicum annuum var. Red chili) towards cow vermicompost application under field conditions.Method Cow vermicompost was supplied in four levels (0, 5, 10, and 15 t ha-1) across the two growing seasons in 2017 and 2018. Results Vermicompost application significantly increased the plant height, internode distance, and the number of lateral branches in both seasons. It was noticed that manuring with 15 t ha-1 of cow vermicompost resulted with enhanced chlorophyll contents, fruit yield, and fruit number in both years. In both seasons, the highest leaf number, fruit weight, and total soluble solids are related to the third treatment (10 t ha-1 of cow vermicompost). The results showed that 1000-seed weight and vitamin C content were affected by cow vermicompost. Data showed that manuring with vermicompost (5 t ha-1) caused the best quality components in 2017 and 2018.Conclusion It was concluded that the application of vermicompost had a significant impact on vegetative and reproductive growth and fruit quality of hot pepper.